Pengaruh Ventilated Frame terhadap Distribusi Temperatur dan Kinerja Panel Surya - Rivan Muhfidin; Wartono; Sumpena; Diah Suwarti Widyastuti (Jurnal Engine: Energi, Manufaktur, dan Material, 2026)
The increase in operating temperature is one of the main factors limiting solar panel performance because it reduces the power output and efficiency of photovoltaic systems. This study aims to analyze the effect of a ventilated frame on temperature distribution, power output, and solar panel efficiency. The research was conducted using an experimental approach with three configuration variations: no frame, conventional aluminium frame (solid frame), and ventilated aluminium frame (ventilated frame). The experiments were carried out for three days under clear weather conditions from 07:00 to 17:00. The measured parameters included solar irradiance, panel surface temperature, voltage, current, and output power. The results showed that panel temperature increased with increasing solar irradiance and reached its peak during midday. The ventilated frame produced a more uniform temperature distribution, reduced panel temperature by approximately 0.5–1.5°C, and improved power output by 1%–3% and efficiency by approximately 0.1%–0.2% compared to the conventional frame. In addition, the efficiency sensitivity to temperature was found to be in the range of 0.07–0.08%/°C, indicating that panel performance is strongly influenced by thermal conditions. These findings demonstrate that the ventilated frame has the potential to serve as an effective passive cooling solution for improving the thermal and electrical performance of solar panels without requiring additional energy and can be applied to existing photovoltaic systems with minimal structural modification.